N-acetylcysteine (NAC) for methamphetamine dependence: A randomised controlled trial. (August 2021) - McKetin, Rebecca; Dean, Olivia M.; Turner, Alyna; Kelly, Peter J.; Quinn, Brendan; Lubman, Dan I.; Dietze, Paul; Carter, Gregory; Higgs, Peter; Sinclair, Barbara; Reid, David; Baker, Amanda L.; et al.
Abstract: Background: Methamphetamine dependence is a significant global health concern for which there are no approved medications. The cysteine prodrug, N-acetylcysteine (NAC), has been found to ameliorate glutamate dysregulation in addiction, and to reduce craving for methamphetamine and other drugs. We evaluated the efficacy and safety of NAC as a pharmacotherapy for methamphetamine dependence. Methods: A parallel double-blind randomised placebo-controlled trial of people dependent on methamphetamine recruited from Geelong, Melbourne and Wollongong, Australia, between July 2018 and December 2019. Participants were randomised to receive either 12 weeks of oral NAC (2400 mg/day) or matched placebo, delivered as a take-home medication. The primary outcome was methamphetamine use, measured in two ways: (a) change in days of use in the past 4 weeks from baseline to weeks 4, 8 and 12, assessed using the Timeline Followback; and (b) methamphetamine-positive oral fluid samples taken weekly. Analyses were intention-to-treat and based on imputed data. Secondary outcomes were craving, severity of dependence, withdrawal severity and psychiatric symptoms (depression, suicidality, hostility and psychotic symptoms). Significance levels were p  < 0.025 for primary outcomes and p  < 0.01 for secondary outcomes. Adverse events were compared between groups by system organ class. The study was prospectively registered, ACTRN12618000366257. Results: Participants ( N  = 153; 59% male, mean [SD] age 38 [8]) were randomised to placebo ( n  = 77) or NAC ( n  = 76). Both groups had a median (IQR) of 24 (15–28) days of methamphetamine use in the 4 weeks prior to baseline. Both groups significantly reduced methamphetamine use (mean [SE] reduction of 7.3 [1.2]) days for placebo, 6.8 [1.2] for NAC) but NAC did not reduce days of methamphetamine use more than placebo (group difference of 0.5 days, 97.5% CI -3.4–4.3). There was no significant effect of NAC on methamphetamine-positive oral fluid samples (placebo 79%, NAC 76%; mean difference -2.6, 97.5% CI -12.6–7.4). NAC did not significantly reduce craving, severity of dependence, withdrawal, suicidality, depression, hostility or psychotic symptoms relative to placebo. Adverse events did not differ significantly between placebo and NAC groups. Interpretation: These findings suggest that take-home oral NAC has no significant effect on methamphetamine use or most clinically related outcomes amongst people who are dependent on the drug. Funding: This research was funded by the Australian NHMRC (Project Grant No. 1128147).